Controller Design for the Pitch Control of an Autonomous Underwater Vehicle - Priyadarshini, L.; Kundu, S.; Maharana, M. K.; Ganthia, B. P. (Engineering, Technology & Applied Science Research, 2022)
In recent years, the Autonomous Underwater Vehicle (AUV) has found its application in a large number of areas, especially in the ocean environment. But due to its highly non-linear nature with six degrees of freedom and the presence of hydrodynamic forces, the equations for AUV control become complex and difficult to design. Hence, in order to overcome this complexity and non-linearity, a reduced-order subsystem is derived for controlling the pitch. Linear Quadratic Regulator (LQR) and Fractional Order PID (FOPID) techniques have been applied for determining the controller for better performance of pitch control in the presence of disturbance.